Family support, need for achievement, and entrepreneurial orientation on entrepreneurial intentions in vulnerable groups - Tentama, Fatwa; Mulasari, Surahma Asti; Sukesi, Tri Wahyuni; Sulistyawati, Sulistyawati; Subardjo, Subardjo (International Journal of Public Health Science (IJPHS), 2024)
This study aims to design and test the goodness of fit of a theoretical model that describes the effect of family support, need for achievement, and entrepreneurial orientation on entrepreneurial intentions with empirical data in the field. Research participation used subjects totaling 66 people from Ngalang village who were female, did not have permanent jobs, and were included in the poor category. Data collection uses four measurement scales: the entrepreneurial intention scale, family support scale, need for achievement scale, and entrepreneurial orientation scale, and is analyzed using partial least square (PLS) via smartPLS 3.0. The results of the study show the formation of a theoretical model of the influence of family support, need for achievement, and entrepreneurial orientation on entrepreneurial intentions that fit with empirical data. Family support has a positive and very significant effect on entrepreneurial intentions, the need for achievement does not affect an entrepreneurial orientation, and entrepreneurial orientation has a positive and very significant impact on entrepreneurial intentions. This research implies that this model can be used as a reference and applied to overcoming economic problems in vulnerable groups.